Mechanical Circulatory Support as a Bridge-to-Transplant Candidacy: When Does It Work?. Issue 4 (1st June 2021) - Zaliznyak, Michael; Stern, Lily; Cole, Robert; Shen, Adriana; Nishihara, Keith; Runyan, Carmelita; Fishman, Alisa; Olanisa, Linda; Olman, Megan; Singer-Englar, Tahli; Luong, Eric; Cheng, Susan; et al.
Abstract : Durable mechanical circulatory support (dMCS) devices can be offered as a bridge-to-transplant (BTT) or as a bridge-to-candidacy (BTC) strategy for candidates with contraindications to transplant listing, including pulmonary hypertension (BTC-PH), morbid obesity (BTC-Obes), social issues (BTC-Soc), or chronic illness (BTC-Illness). An understanding of the trajectory of BTC patients could guide future triage of advanced heart failure patients who are not candidates for transplantation. We performed a retrospective review all patients who underwent dMCS implantation as either BTT (206 patients) or BTC (114 patients) at our center from January 1, 2010, to March 31, 2020. There was no significant difference in mortality between BTC patients and BTT patients. Compared with the BTT group, significantly more patients in the BTC-PH group were transplanted (81% vs. 63%; p < 0.05) and significantly fewer patients in the BTC-Obes group (44%; p < 0.05) and BTC-Soc group (39%; p < 0.05) were transplanted. Additionally, the readmission rate was higher for those in the BTC-Obes (6.2 vs. 2.1; p < 0.05) and BTC-Soc (3.9 vs. 2.1; p < 0.05) groups. Bridge-to-candidacy patients generally had poorer post-dMCS trajectories than BTT patients. Centers should not be dissuaded from pursuing a BTC strategy for qualified patients; however, careful consideration of potential adverse outcomes is necessary.